Être une historienne engagée aujourd’hui - Mathilde Larrère; Jean-Charles Buttier (Cahiers d’histoire)
From the occupied universities to the « yellow vests » movement, « Nuit debout » and the protests against the Labor Law, Mathilde Larrère has been in the thick of the main social movements over the past years. She has been both part of it and a witness, not only through her teaching, but also through all her interviews she gave on the media and social networks. From a thorough analysis of the modes of expressions of the « gilets jaunes », she showes how the history of the conflicts and the revolutions can be an inspiration to the present-day struggles. It is through the constant link between her knowledge of the past and her involvement in the present, her thoughts and her actions, her political choices and her professional practice, that she can consider herself as a polically engaged historian.